Espaço, conflito e poder na cidade pós-clássica: João Crisóstomo e a cristianização de Constantinopla (398-404) - Furlani, João Carlos (2022)
In this thesis, we investigate the mechanisms and strategies used to transform the ancient city into a space of devotion suitable for Christians, during the process called Christianization of the Roman Empire. For that, we chose as a case study the city of Constantinople under the episcopate of John Chrysostom (398-404). We argue that Chrysostom’s experience as bishop of the Capital makes it possible to understand nuances of appropriation and resignification of the polis by Christians. We seek to demonstrate that Christianization was a slow and uneven process in time and space, resulting from a series of factors. Among them, the influence on urban space and daily life and the formulation of isotopies and heterotopias, that is, places of identity and otherness, were essential for the construction of an urban landscape closer to the different Christian precepts. At the same time, we also tried to show that the bishops played a leading role, insofar as they represented a group, occupied a position capable of influencing decisions of an administrative and dogmatic nature, found legitimacy in the Christian community and often acted beyond the strictly religious, which gave them a strategic and fundamental position for the Christianization of the cities. Through John Chrysostom’s homilies, as well as works by other ancient authors and material culture, we carried out an investigation into Chrysostom’s discourse and practices concerning the city space, which includes representations of sacred places and dangerous places for Christians, as well as actions aimed at transforming the urban landscape and the daily life of the Congregation of Constantinople, which is why the preacher got into several political-religious conflicts during the years of his episcopate. A series of concepts were mobilized for our investigation, among which we can highlight those of leadership, conflict, space, landscape, city, isotopy, heterotopia, memory and representation, in addition to content analysis method. Therefore, through the actions of John Chrysostom at the head of the see of Constantinople, supported by his leadership position and by his support networks, it is possible to understand more clearly the process of appropriation and resignification of urban environments during the course of the Christianization and dynamics between space and daily life in the late-antique period, a dynamic that involved conflicts and power disputes between the groups that made up the city, which includes different religious aspects and imperial power.